Peran Layanan Bimbingan dan Konseling dalam Mengatasi Permasalahan Peserta Didik di SMA Berdasarkan Tinjauan Literatur - Rafeylah Areefa Elya; Risma Anita Puriani (Lembaga Pengembangan Kinerja Dosen, 2026)
Adolescence is a transitional period marked by rapid biological, psychological, and social changes, which often lead to various problems for individuals, particularly at the high school level. This study aims to analyze the role of guidance and counseling services in addressing these issues using a literature review approach. The method employed is a systematic literature review of relevant scientific publications from 2020 to 2026. The data collection process was carried out through the search, selection, and evaluation of literature related to student issues and guidance and counseling services in schools. The research findings indicate that students face various challenges, such as difficulties in learning, low academic ability, academic stress and anxiety, as well as social-emotional issues influenced by internal and external factors. Guidance and counseling services play a role in supporting students to self-reflect, overcome problems, and optimize their potential through preventive, curative, and developmental approaches. The success of these services is also supported by the role of counselors, collaboration with other teachers, and parental participation. However, in practice, there are still a number of obstacles, such as limited human resources, a lack of coordination, and an incomplete understanding of the functions of these services. Therefore, efforts are needed to improve implementation and cooperation so that guidance and counseling services can operate more efficiently.